Realization of Profil Pelajar Pancasila Based on Project Learning in Vocational Education at Tamansiswa, Indonesia - Nur Kholifah; Muhammad Nurtanto; Farid Mutohhari; Triyanto; Ida Nugroho Saputro; Alias Masek (Qualitative Research in Education, 2025)
Project-Based Learning (PBL) is a recommended method in vocational education, particularly for implementing the Profil Pelajar Pancasila (P3). However, learning that emphasizes character values aligned with the "Budaya Luhur Ajaran Tamansiswa" remains limited, and there has been a decline in soft skills among vocational graduates in the 21st century. This study explores the perceptions of educational and cultural practitioners and vocational teachers in implementing P3 using the PBL approach in Tamansiswa, Indonesia. A total of 12 key informants were selected using purposive sampling techniques. Data from observations, interviews, and Focus Group Discussions (FGD) were thematically analyzed using Nvivo 12 Plus software. The findings revealed three themes: planning, implementation, and evaluation. The PBL stages included problem analysis, project planning, coordination of execution, product creation and its progress, and evaluation of results while ensuring student engagement in Ngerti, Ngrasa, Ngalakoni. Vocational learning emphasizes the balance of intellectual, emotional, creative, and physical development, reflected in the pillars of character to shape individuals who are independent, competitive in the workplace, and adaptive in modern society.